Urea efficiency in maize (Zea mays var. saccharata) under sulphur treatment in an alkaline soil - Ithnin, Muhammad Nurhadi (2015)
Malaysian soils are known to be acidic and highly weathered and fall under the orders of Oxisols and Ultisols. There are locations in Malaysia where the soils are alkaline and they are usually found near and in close proximity to mountains and hills that are of limestone. Limestone hills in Ipoh, Gua Musang, Langkawi and Niah could have soils in their vicinity having alkaline pH. Melangit series that is located at Bukit Bintang, Kangar, Perlis is an example of such an alkaline soil. This soil series is located near a limestone hill and has a pH reading of 7.8. The problem that is related with alkaline soil is the deficiencies of some nutrients including nitrogen (N), phosphorus (P) and micronutrients. This study was conducted to investigate the urea efficiency uptake in maize under sulphur (S) treatments in an alkaline soil and to observe the growth of maize plant grown on an alkaline soil with S treatments. The hypothesis of this experiment is that the pH of the alkaline soil will be lowered due to the S treatments and thus will increase the effectiveness of nitrogen uptake from urea by plant. This experiment was conducted under glasshouse condition. The experimental design is randomized complete block design (RCBD). An amount of 3kg soil was used for each pot with one plant to each pot and was treated with 4 rates of sulphur (0g, 2.5g, 5g, and 10g per 1kg of soil). After a month, the source of nitrogen in the form of urea fertilizer was applied to the soil. Urea fertilizer was added to the soil at two rates (0g and 120 kg/ha) and maize seeds were planted. Normal rate of P and K fertilizer for maize were applied to all pots. The plants were harvested after 35 days of planting. The fresh weight and dry weight of all plant parts were recorded. The soil pH was determined. The concentrations of nitrogen and sulphur in the soils and in the plants were determined. In this experiment, there is an interaction between sulphur and urea to the soil pH. The result shows that there is a decrease in pH of the soil which affects the urea efficiency uptake by plant. A large difference of treatment S15 with other treatments was shown in the nitrogen content in the soil. It is expected that the S treatments result in increased efficiency of the Urea fertilizer used. The high percentage of nitrogen content also results in high efficiency of nitrogen uptake by the plant (5.52% efficiency). The growth of the plant also corresponds to the different amount of sulphur applied. As for the conclusion, application of sulphur and urea showed an interaction to the soil pH, and show a positive result on the plant dry weight, availability of nitrogen in soil, and nitrogen efficiency uptake by plant.